Next-gen therapeutics to spare and expand beta-cell mass. (December 2021) - Bolla, Andrea Mario; Usuelli, Vera; Ben Nasr, Moufida; Frigerio, Sofia; Loretelli, Cristian; D'Addio, Francesca; Fiorina, Paolo
Abstract: The most effective and physiological way to treat hyperglycemia is to restore beta-cell function and to rescue production of endogenous insulin. Increasing evidence suggests that both type 1 and type 2 diabetes are characterized by a significant defect in beta-cell mass, leading to the manifestation of the disease. Novel alternative approaches are needed to spare and expand beta-cell mass in patients with diabetes. This review sets out to describe the latest findings on how to restore the beta-cell mass and function in both forms of diabetes to modulate their progression.